Financial Performance in Energy Companies: The Role of Green Accounting, Sustainability Reports, and Earnings Management on the Indonesia Stock Exchange - Riska Natariasari; Ananta eda claudya; Rheny Afriana Hanif (Academic Bright Collaboration, 2026)
Purpose – This research assesses the financial performance which proxied by Return on Assets (ROA) of listed energy sub-sector firms between 2021 and 2024. It specifically isolates the impacts of green accounting, sustainability reports, and earnings management on those corporate outcomes. Methods – The study employed a quantitative approach, gathering secondary data from companies’ financial statements and sustainability reports. The sample consists of 40 companies selected via purposive sampling and analyzed by descriptive statistics and multiple linear regression via IBM SPSS version 29. Findings – The results indicate that green accounting and earnings management have a significant yet negative impact on corporate financial performance. Meanwhile, sustainability reports were not found to influence financial performance. These findings demonstrate that not all hypotheses are empirically confirmed, particularly from the perspective of short-term corporate financial performance; however, they become more relevant in the long-term perspective. Research Implications – This study contributes by examining the combined effects of green accounting, sustainability reports, and earnings management on financial performance in the energy sector using recent data from 2021–2024, reflecting post-pandemic conditions and evolving sustainability policies. Originality – This study successfully integrates green accounting, sustainability reports, and earnings management into a single model within the energy sector, thereby providing an empirical contribution to the examination of the relationship between sustainability practices and financial performance.